1996
DOI: 10.1002/(sici)1097-0142(19960801)78:3+<654::aid-cncr10>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for pancreatic carcinoma

Abstract: BACKGROUND Pancreatic cancer is an aggressive disease and its patients typically have a short survival, usually marked by pain and rapid debilitation. The disease has been considered relatively chemoresistant, although many chemotherapy regimens have been described. METHODS Clinical results with chemotherapy, since the first publication of response in 1960, were reviewed for efficacy and toxicity. Emphasis was given to prospective trials with adequate power and clear evaluation criteria and end‐points. RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…4 Even if resection can be undertaken, recurrence at the original site of the tumour shortens survival. 5,6 Despite recent developments, 7,8 conventional chemotherapy, using drugs such as cisplatin, 5-fluorouracil, taxol and more recently gemcitabine, has had limited success in the clinic since the necessary high local drug doses cannot be achieved without significant systemic toxicity. 3,5,8 Novel chemotherapeutic prodrugs might offer a way round these toxicity problems if they could be activated locally.…”
Section: Introductionmentioning
confidence: 99%
“…4 Even if resection can be undertaken, recurrence at the original site of the tumour shortens survival. 5,6 Despite recent developments, 7,8 conventional chemotherapy, using drugs such as cisplatin, 5-fluorouracil, taxol and more recently gemcitabine, has had limited success in the clinic since the necessary high local drug doses cannot be achieved without significant systemic toxicity. 3,5,8 Novel chemotherapeutic prodrugs might offer a way round these toxicity problems if they could be activated locally.…”
Section: Introductionmentioning
confidence: 99%
“…In all, 80 -95% of patients are inoperable at diagnosis and only about 1% of patients are still alive 5 years from the time of diagnosis (Ahlgren, 1996). Gemcitabine (2 0 ,2 0 difluorodeoxycytidine), a nucleoside analogue with a mild toxicity profile (Aapro et al, 1998), has been shown to improve both clinical benefit and survival in patients with advanced pancreatic cancer compared to treatment with 5-fluorouracil, although overall survival was poor with a median survival of less than 6 months (Burris et al, 1997).…”
mentioning
confidence: 99%
“…Third, from our small trial it remains unclear as to whether the survival length of our patients achieving SD is due to the specific antitumour treatment or might have been achieved with best supportive care alone. Whereas the superiority of a specific antitumour treatment over best supportive care has been demonstrated for other highly aggressive tumours (Ahlgren, 1996;Scheithauer et al, 1999;Hoffman and Glimelius, 1998;Burris et al, 1997), meta-analyses from randomized trials using doxorubicin for HCC did not reveal any survival benefit (Mathurin et al, 1998;Simonetti et al, 1997). However, these data were generated from the treatment with the free drug doxorubicin.…”
Section: Discussionmentioning
confidence: 99%